PEMBENTUKAN KARAKTER ANAK USIA DINI BERBASIS KOMUNIKASI INTERPERSONAL DENGAN PENDEKATAN BEYOND CENTER OF CIRCLE TIME (PENDAMPINGAN KADER POS PAUD DESA PACIRAN KABUPATEN LAMONGAN) - Musrifah Musrifah (JCE (Journal of Childhood Education), 2021)
One of the developmental tasks that must be completed in early childhood is language development. Often we find that early childhood is well developed biologically but has not developed well in its developmental tasks. Language skills do not just come, but like other abilities, they must be cultivated and developed so that they are in accordance with the proper stages of development. Children's communication with the adults around them has a very significant role in shaping children's character. Moral values and general knowledge can only be received well by early childhood if they are communicated with the right kind of communication. Openness, empathy and richness of language and motivation from adults when accompanying children to play are the conditions for effective interpersonal communication between the two. Effective communication produces effective learning outcomes as well. Not a few teachers and guardians of students have serious problems communicating with early childhood because of the lack of understanding of early childhood thinking and learning which affects language development. This activity took place at the PAUD POS in Paciran Village, Lamongan Regency, where most of the population are fishermen families with an average education level equivalent to SMP and SMA. The concrete experiences that participants get in this activity are practicing effective communication methods in early childhood in learning experiences through play. With direct guidance and practice, it is hoped that participants can optimize their role as facilitators, motivators and evaluators for language development and other intelligence development for early childhood.